1996
DOI: 10.1021/bi9520500
|View full text |Cite
|
Sign up to set email alerts
|

Evidence Favoring Molybdenum−Carbon Bond Formation in Xanthine Oxidase Action:  17O- and 13C-ENDOR and Kinetic Studies

Abstract: The reaction mechanism of the molybdoenzyme xanthine oxidase has been further investigated by 13C and 17O ENDOR of molybdenum(V) species and by kinetic studies of exchange of oxygen isotopes. Three EPR signal-giving species were studied: (i) Very Rapid, a transient intermediate in substrate turnover, (ii) Inhibited, the product of an inhibitory side reaction with aldehyde substrates, and (iii) Alloxanthine, a species formed by reaction of reduced enzyme with the inhibitor, alloxanthine. The Very Rapid signal w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
111
2
3

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(125 citation statements)
references
References 59 publications
(136 reference statements)
9
111
2
3
Order By: Relevance
“…Using EPR and electron-nuclear double resonance (ENDOR) spectroscopy in conjunction with 17 O labeling methods, it has been convincingly demonstrated that the MoOOH group is the catalytically labile oxygen (10,11). On the basis of these results, two quite different reaction mechanisms have been proposed, with the reaction proceeding either by base-catalyzed nucleophilic attack of MoOOH on the C-8 position of the substrate (leading directly to the product coordinated to the now-reduced molybdenum via the newly introduced hydroxyl group) (11), or alternatively by addition of the C8OH bond across the MoAS group of the molybdenum center, followed by oxygen insertion to yield an intermediate with a direct MoOC bond (10). The work presented here provides direct information regarding the structure of the initially formed intermediate in the catalytic sequence and demonstrates that this intermediate has the product coordinated to molybdenum in a simple end-on fashion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using EPR and electron-nuclear double resonance (ENDOR) spectroscopy in conjunction with 17 O labeling methods, it has been convincingly demonstrated that the MoOOH group is the catalytically labile oxygen (10,11). On the basis of these results, two quite different reaction mechanisms have been proposed, with the reaction proceeding either by base-catalyzed nucleophilic attack of MoOOH on the C-8 position of the substrate (leading directly to the product coordinated to the now-reduced molybdenum via the newly introduced hydroxyl group) (11), or alternatively by addition of the C8OH bond across the MoAS group of the molybdenum center, followed by oxygen insertion to yield an intermediate with a direct MoOC bond (10). The work presented here provides direct information regarding the structure of the initially formed intermediate in the catalytic sequence and demonstrates that this intermediate has the product coordinated to molybdenum in a simple end-on fashion.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, the oxygen atom at the catalytically labile site on the Mo center is transferred to a substrate and is subsequently regenerated by oxygen derived from the solvent before a second round of catalysis (9). Alternative mechanisms in which either the MoAO or MoOOH group represents the catalytically labile group have been proposed in the past (2,10,11). In the present work, we have determined the crystal structure of the first and key reaction intermediate of this unique molybdenumbased hydroxylation chemistry by using a slow substrate; the results allow us to draw further conclusions about the catalytic mechanism.…”
mentioning
confidence: 85%
“…Similarly, Wedd and coworkers (17) suggested earlier that a metal-coordinated hydroxide rather than MoϭO might represent the catalytically labile oxygen site of xanthine oxidase on the basis of EPR studies of model compounds. Recently, Bray and co-workers (18) inferred from an ENDOR study of the "very rapid" EPR signal that the MoϭO group does not exchange with solvent in the course of catalysis (on the basis of their inability to detect a second, weakly coupled 17 O nucleus in addition to the strongly coupled 17 O of bound product) and concluded that Mo-OH rather than MoϭO is the catalytically labile oxygen site. The failure to detect a weakly coupled oxygen in this experiment is not surprising, however, given the intrinsically weak spectral signature of even a strongly coupled oxygen and the difficulty of identifying a second, more weakly coupled nucleus in the presence of a more strongly coupled one.…”
Section: Discussionmentioning
confidence: 99%
“…In light of the known precedence for oxo transfer in the literature of small inorganic complexes of molybdenum (7)(8)(9)(10)(11)(12)(13)(14)(15)(16), it was originally thought most likely that the catalytically labile site of the enzyme was the MoϭO group. More recently, it has been suggested that the catalytically labile site might instead be a metal-coordinated hydroxide (17)(18)(19). Given the crystallographic demonstration that water/hydroxide is a li-gand to the active-site metal in this family of molybdenumcontaining enzymes (19,20), this mechanistic possibility must be considered.…”
mentioning
confidence: 99%
“…Howes et al have proposed a rather different mechanism from ENDOR studies on the paramagnetic catalytic intermediate called "very rapid" ( Figure 1e). 14 It involves addition of the substrate CH group across the ModS bond, a reaction with chemical precedent, 15 and simultaneous proton abstraction by the sulfido ligand. This reaction is proposed to be initiated through an electrophilic attack by Mo on the substrate C atom and attack by the OH x ligand to give the product of the reaction (a CdO group) coordinated to Mo in a η 2 fashion.…”
Section: Introductionmentioning
confidence: 99%